Acute Toxicity Test of Soursop Leaves (Annona muricata) on Liver and Kidney of Switzerland Mice - Utomo, Astika Widy; Susilaningsih, Neni; Armalina, Desy (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2015)
Introduction: The soursoup leaves extract (Annona muricata) has widely been used as traditional medicine for cancer. No studies have been conduct to investigate the safety of the extract. Objectives: The purpose of the study was to investigate the acute oral toxicity test of soursoup leaves extract (Annona muricata) on Swiss mice’s liver and kidney.Methods: Twenty four mice were divided into 4 groups. Group I was control group, while group II-IV was given soursoup leaves extract as single dose orally via sonde. The mice were obsereved until day 7 to determine the LD50 and at the end were terminated to collect the liver and kidney. The organs later were made into histopathology slides. The slides read with light microscope. The data analyzed with ANOVA and was considered significant at p<0.05.Results: All mice were alive during the 7 days observation and no mice showing the toxic spectrum after the dosing. Microscopically, no damage on the liver and kidney organ among the groups.Conclusion: The LD50 of soursoup leaves extract is more than 2000 mg/kgBW. This result indicate that the extract is practically non toxic and do not damage the liver and kidney.